DOI: 10.47328/ufvbbt.2021.132
|View full text |Cite
|
Sign up to set email alerts
|

Análise de imagens na caracterização biométrica e avaliação da carcaça de bovinos

Abstract: O processo de tipificação determina o mercado para o qual a carcaça será direcionada, considerando sua qualidade. Atualmente, este processo é desenvolvido de maneira subjetiva, e, portanto, a confiabilidade desse pode ser comprometida. Neste sentido, ferramentas que permitam a avaliação objetiva da carcaça bovina in vivo e post mortem são de grande importância. Diante disso, nossos objetivos neste trabalho são (1) avaliar o efeito da classe sexual sobre a morfologia corporal ou de carcaças em bovinos e investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
6

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 91 publications
(111 reference statements)
0
6
0
6
Order By: Relevance
“…Brasileiro ( 2023) evaluated the goodness of fit of the BFT equation proposed by Assis (2021). Validation database was composed of 43 treatment means from 16 published studies (Table 6.10).…”
Section: Validation Of Backfat Thickness Predictive Equationmentioning
confidence: 99%

Nutrient Requirements of Zebu and Crossbred Cattle - BR-CORTE

Sebastião de Campos,
Douglas Teixeira,
Pedro Del Bianco
et al. 2023
“…Brasileiro ( 2023) evaluated the goodness of fit of the BFT equation proposed by Assis (2021). Validation database was composed of 43 treatment means from 16 published studies (Table 6.10).…”
Section: Validation Of Backfat Thickness Predictive Equationmentioning
confidence: 99%

Nutrient Requirements of Zebu and Crossbred Cattle - BR-CORTE

Sebastião de Campos,
Douglas Teixeira,
Pedro Del Bianco
et al. 2023
“…Inc., Cary, NC), and 0.05 was established as the critical level of probability for a type I error. More details regarding this study can be found in Assis (2021).…”
Section: Estimation Of Backfat Thicknessmentioning
confidence: 99%
“…However, interactions between genotype and gender were found for the coefficient associated with the CW predictive variable. Thus, Assis (2021) suggested the following BFT predictive equation: BFT (mm) = -2.37 + 0.709 × ADG + CW × G (R² = 0.49, RMSE = 1.67) Eq.6. Brasileiro (2023) evaluated the goodness of fit of the BFT equation proposed by Assis (2021).…”
Section: Estimation Of Backfat Thicknessmentioning
confidence: 99%
See 2 more Smart Citations